Citizen journalism gatekeeping process: An evaluation of conceptual framework for computer mediated communication (CMC) hoax interactivity - Lani, Oktri Permata; Putra, Fauzi Eka (Universitas Bunda Mulia, 2024)
Compliance with the Journalistic Code of Ethics (KEJ) is very important and mandatory for journalistic workers. Nowadays, we often encounter journalistic works that are unethical and tend to be very unethical, thus making the connoisseurs of journalistic works uncomfortable with them. This phenomenon can be found on the New Media news portal which spreads various kinds of hoax information. Freedom in the use of New Media is one of the reasons why hoaxes usually appear in New Media, because those who inform news are not only from the journalist profession. While a journalist will pay attention to the Journalistic Code of Ethics (KEJ). In addition, there is no official institution that functions to control and supervise the dissemination of information in New Media. Unlike the case with the mass media which is always monitored by KPI as the Gatekeeper of broadcasting in Indonesia. So that it can filter out various information that is not worthy of appearing in the circulation of journalistic work connoisseurs. Therefore, those who play an important role in New Media to be able to filter all circulating information or in other words who become Gatekeepers are connoisseurs of journalistic work themselves. So that later journalistic connoisseurs will not be consumed by hoaxes and not spread hoaxes. So that the existence of this phenomenon makes researchers interested in studying it more deeply about it. This study uses qualitative methods, data collection techniques in the form of observation, interviews, and documentation, and the validity of the data using time and source triangulation.